PENERAPAN METODE BERMAIN PERAN UNTUK MENINGKATKAN KEMAMPUAN MENYIMAK ISI CERITA RAKYAT BAGI SISWA KELAS V SD INPRES 1 PARANGGI KECAMATAN AMPIBABO - Anwar, Anwar (BAHASANTODEA, 2016)
Scrutinize learning is listening proses of oral symbols expressly and carefully and also with understanding, apreciation, interpretation, reaction, and evaluation to get a message, information, content and the meaning in there. The problem formula of this research are (1) how is the application role play method to improve ability in  scrutinize  content folklore at fifth grade students of SD Inpres 1 Paranggi Kecamatan Ampibabo? (2) how is the improvement result of application role play method to improve ability in  scrutinize  content folklore at fifth grade students of SD Inpres 1 Paranggi Kecamatan Ampibabo?. this research has aim to (1) describe application role play method to improve ability in  scrutinize  content folklore at fifth grade students of SD Inpres 1 Paranggi Kecamatan Ampibabo, (2) describing result of application role play method to improve ability in  scrutinize  content folklore at fifth grade students of SD Inpres 1 Paranggi Kecamatan Ampibabo. This research has two cycles, each of cycle has implemented two meetings in the class and each cycle consist of four steps, there are planning, implementing, observation and reflection. The indicator of individual achievement is 67% and the classical completeness is 80%. The assesment component of scrutinize folklore that is accuracy to telling the content of story, accuracy analysis of character in a story, writing the background of the story which listened and conclude the content of story. Based on the poduct, the improvement of students scrutinize ability can be seen based on the data analysis of improvement students scrutinizing. He result of cycle 1, individual completeness achieve 65,5% and classical comleteness 71,4%. Result of the research at cycle II had a significance improvement, individual completeness achieve 80,95% and classical completeness achieve 100%. Therefore, it can be concluded that learning with role play method can improve scrutinize ability of folklore  content story at the fifth grade students of SD Inpres 1 Paranggi, Kecamatan Ampibabo.